The Scientific Development of the Physiology of Plants in the American Tropics - Gutiérrez, Marco V (Universidad de Costa Rica, 2002)
This paper is a research and journalistic work that summarizes and synthesizes the scientific development of the physiology of plants in the American tropics, also known as the Neotropics. It contains the contributions of numerous biologists interested in the physiology of tropical plants. The fabulous structural and functional diversity of tropical forests is still the major driver of research in this field. Classical physiological work involving tropical plants, such as the discovery of C4 photosynthesis in sugarcane, is invoked to exemplify the historical and current importance of physiological research in the tropics, and its applications in agriculture, forestry and conservation. An historical background describing the early and more recent development of a tradition on the physiological study of tropical plants is followed by a summary of the research conducted on the physiology of tropical crops. Common areas of interest and influence between the fields of crop physiology and plant ecophysiology are identified and exemplified with problems on the environmental physiology of crops like coffee and cassava. The physiology of tropical forest plants is discussed in terms of its contributions to general plant physiological knowledge in areas such as photosynthetic metabolism and plant water relations. Despite the impressive technical advances achieved during the past decade, the importance of continuous development of appropriate instrumentation to study and measure the physiology of plants in situ is stressed. Although the basic metabolic processes that underlie the mechanisms of plant responses to the environment are probably highly conserved and qualitatively similar among tropical and temperate plants, it is also apparent that tropical plants exhibit metabolic peculiarities. These include aspects of photosynthetic metabolism, phloem transport physiology, sensitivity to low temperatures, reproduction, responses to climatic seasonality, and a large variety of biotic interactions. Old and new paradigms are examined in light of recent evidence and comparative studies, and the conceptual and technical advances needed to foster the development of tropical plant ecophysiology are identified.